Investigating the linkages between Indo-Pacific Ocean SST, Z500 climate variability and Tasmanian seasonal streamflow - Shams, Md Shamim; Anwar, Faisal; Lamb, Kenneth (2017)
Seasonal floods occur predominantly in Tasmania at any time of the year (STORS, 2006). Improved streamflow predictability can be helpful for better Tasman seasonal flood forecasting and flood management in the rise of potential recent decade’s climate change pattern. The present study focuses on evaluating the relationship between the Indo-Pacific Ocean and large continental ocean-atmospheric climate variability and with seven Tasmania river basins for around 42 years (1971~2012). The statistical technique named singular-valued decomposition (SVD) was applied on a standardized dataset for sea-surface temperatures (SST), 500mb geopotential height (Z500) and 7 unimpaired Tasmanian river streamflow. The result identified the significant ocean-atmospheric regions (90% significance level) that influence hydrology of the Tasmanian rivers and subsequently lead to flood forecasts. SVD results showed that SST performed better seasonal variability in Tasman streamflow compared to Z500, particularly during the winter season. But both the climate indices identify a significant southward trend region around the longitudes 175°W to 140°W and latitudes 25°S to 35°S which has better correlation with Tasman seasonal streamflow. This identified hypothesized region can be used as the probable driver of the Tasman basin streamflow. Understanding this correlation may provide better accuracy for long-lead river flood forecasting.